A cicatriz não é invisível: uma análise das violências de gênero contra mulheres lésbicas na cidade de Manaus - (:unkn) unknown (Universidade Federal do Amazonas, 2024)
The present dissertation aims to reflect on and examine the various manifestations of violence faced by lesbian women throughout their trajectories, from childhood to family interactions, in the social sphere, and within marital relationships. Additionally, it aims to demonstrate how these women cope with traumas related to lesbophobia and intimate partner violence. To this end, a study was conducted through semi-structured interviews with five women of different age groups, all identified as lesbian and residents of the city of Manaus, Amazonas, Brazil. Employing an intersectional approach, I analyze the narratives and complex processes of violence experienced by these women. Furthermore, theoretical conceptions regarding the phenomenon of violence are debated, considering it as polysemic. It was found that psychological violence was the most pronounced among the interviewees, although other forms of violence were also reported, such as physical, economic, sexual, and moral.
The Scar Is Not Invisible: An Analysis of Gender-Based Violence Against Lesbian Women in the City of Manaus
Keywords: .; .; .; CIENCIAS HUMANAS: ANTROPOLOGIA; Lesbianidade; Gênero e sexualidade; Violência contra a mulher